The Dynamics of U.S. Internal Migration - Treyz, George I.; Rickman, Dan S.; Hunt, Gary L.; Greenwood, Michael J. (The Review of Economics and Statistics, 1993)
In this paper the authors have theoretically derived a net migration equation and estimated it using time-series data for 51 regions over the period 1971-88. The results indicate that the dynamic response of net migration is stable and is significantly related to stock equilibrium changes induced by amenity differentials, relative employment opportunities, relative real wages, and industry composition. Moreover, the explicit linkage of stock equilibrium to stable dynamic flows in the model ensures that any stock disequilibrium will generate a finite migration response sufficient to attain a new stock equilibrium. The estimated parameters determine the speed at which net migration re-establishes stock equilibrium. Coauthors are Dan S. Rickman, Gary L. Hunt, and Michael J. Greenwood. Copyright 1993 by MIT Press.